2023
DOI: 10.3389/fonc.2023.1066360
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive nomogram combining CT-based radiomics with clinical features for differentiation of benign and malignant lung subcentimeter solid nodules

Abstract: ObjectiveTo establish a nomogram based on non-enhanced computed tomography(CT) imaging radiomics and clinical features for use in predicting the malignancy of sub-centimeter solid nodules (SCSNs).Materials and methodsRetrospective analysis was performed of records for 198 patients with SCSNs that were surgically resected and examined pathologically at two medical institutions between January 2020 and June 2021. Patients from Center 1 were included in the training cohort (n = 147), and patients from Center 2 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
(47 reference statements)
0
0
0
Order By: Relevance
“…One study identified a radiomic signature discerned from conventional CT that reached an AUC of 0.92 for overall survival in a validation set of patients with melanoma treated with pembrolizumab [13]. Similar studies have demonstrated the effectiveness of CT-based radiomic signatures in predicting overall survival in patients with NSCLC treated with nivolumab [29]. Such signatures can be developed for other imaging modalities, such as FDG-PET scans.…”
Section: Response Assessmentmentioning
confidence: 90%
“…One study identified a radiomic signature discerned from conventional CT that reached an AUC of 0.92 for overall survival in a validation set of patients with melanoma treated with pembrolizumab [13]. Similar studies have demonstrated the effectiveness of CT-based radiomic signatures in predicting overall survival in patients with NSCLC treated with nivolumab [29]. Such signatures can be developed for other imaging modalities, such as FDG-PET scans.…”
Section: Response Assessmentmentioning
confidence: 90%
“…Several prediction models, such as the Mayo model [ 10 ], the VA model [ 11 ], the Brock model [ 12 ], and the PKUPH model [ 13 ], have been designed for evaluating benign and malignant pulmonary nodules. Partial prediction models have incorporated advanced quantitative imaging methods, including CT attenuation, tumor diameter growth rate, and imaging omics [ 15 , 22 , 23 ]. However, all these classical models have certain limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Within thoracic radiology, radiomic techniques have been extensively explored for their potential to distinguish benign and malignant lesions, predict tumor classification, and assess treatment outcome [8‒11]. The combination of radiomic features with clinical factors has shown promise in improving the accuracy of disease diagnosis [12]. However, there is a notable gap in the existing research regarding integrating radiomic features and clinical factors to construct a radiomic-clinical combined model specifically for distinguishing the nature of PE.…”
Section: Introductionmentioning
confidence: 99%